Effect of the intermediate quenching on fracture toughness of ferrite-martensite dual phase steels (Fracture and Structural Integrity, 2020)
The main aim of the research work is to examine the fracture toughness of the dual phase steels prepared using the intermediate quenching method. The ferrite-martensite dual phase (DP) steel is produced using low carbon micro alloyed steel by the heat treatment and intercritical quenching technique using various intercritical temperatures such as 740,760,780,800 and 820oC. The samples of the produced dual phase steel are analyzed for their microstructure using optical microscope. The fracture toughness investigations for the dual phase steel have been carried out using ASTM standard testing procedure. From the results it is observed that the fine distribution and equal volume fraction of ferrite and martensite phases at 780oC. The effect of which, the A780 steel has demonstrated excellent fracture toughness which is the result of intermediate quenching technique. The fractography analysis it is clear that the ductile initiated brittle fracture is occurred which is due to the increased hard martensite phase and the increment in the stress accumulation at the ferrite which also leads to the higher elongation.
Keywords: Martensite; Ferrite; Intercritical temperature; Volume fraction; Dual phase steel; Fracture toughness